An automatic irrigation system for plants using fuzzy logic controller considering volumetric water content. (January 2020) - Rahim, S.; Hussain, M H; Rahim, S R A; Hashim, N; Halim, H A
Abstract: An automatic irrigation system have an important role in today agriculture sector. Currently, automatic irrigation systems which can irrigate and supply plants with desired level and amount of water required for normal plant growth are not available. Furthermore, the classical method using on-off controller is inefficient due to results in loss of energy and productivity. Thus, an efficient automatic irrigation system with fuzzy logic controller is proposed to estimate the amount of water level using the irrigation model, soil type and type of plant. This paper presents a solution for irrigation system for plants using fuzzy logic controller using MATLAB Simulink. To indicate the effectiveness of the proposed method, on-off controller method is also applied for validation purpose.